2008
DOI: 10.1111/j.1523-5378.2008.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and Antrum Erosion‐Specific Gene Expression Patterns: The Discriminative Role of CXCL13 and VCAM1 Transcripts

Abstract: Whole genomic microarray analysis yielded new H. pylori infection and erosion-related gene expression changes. Discriminative genes can be used in mRNA-based diagnostic classification of gastric biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
22
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 39 publications
6
22
1
1
Order By: Relevance
“…In H. pylori-associated gastritis, recruitment of T-and B cells, dendritic cells and neutrophil granulocytes is mediated by a variety of chemokines interacting with their cognate receptors such as CCR7, CCR5, CXCR1 and CXCR4 expressed on infiltrating immunological cells. 30,[36][37][38][39][40][41] Consistent with these findings, we also observed upregulated mRNA transcripts of CCR8, CCR9, CXCR3 and CXCR7.…”
Section: Discussionsupporting
confidence: 90%
“…In H. pylori-associated gastritis, recruitment of T-and B cells, dendritic cells and neutrophil granulocytes is mediated by a variety of chemokines interacting with their cognate receptors such as CCR7, CCR5, CXCR1 and CXCR4 expressed on infiltrating immunological cells. 30,[36][37][38][39][40][41] Consistent with these findings, we also observed upregulated mRNA transcripts of CCR8, CCR9, CXCR3 and CXCR7.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to IL-8, the chemokines CXCL1, CXCL2, and CXCL3 are involved in neutrophil attraction (51), whereas CCL20 attracts immature dendritic cells and memory T cells and plays a role in inflammation on mucosal surfaces (45). In support of previous reports (38,39,(41)(42)(43)(44)(45)(46), we detected increased levels of IL-8, CXCL1, CXCL2, CXCL3, and CCL20 in gastric antrum biopsies from patients infected with H. pylori compared with H. pylori-negative patients. Although ICAM1 expression was detected in all biopsy samples, no statistically significant difference was observed between the two patient groups.…”
Section: Discussionsupporting
confidence: 88%
“…CXCL2 and CXCL3 chemokine secretion was not assayed, because ELISA kits for these proteins were unavailable. Similarly to previous reports (38,39,(41)(42)(43)(44)(45)(46), we detected increased levels of IL-8, CXCL1, CXCL2, CXCL3, and CCL20 in gastric antrum biopsies from H. pylori-positive patients compared with H. pylori-negative patients (Supplemental Fig. 1).…”
Section: H Pylori Lps Induces Il-8 Expression Via Tlr2supporting
confidence: 89%
“…These findings suggest that follicular DCs are a specialized form of myofibroblast and, instead, myofibroblasts characterized by a-SMA may produce CXCL13. [26]. On the other hand, the prior [22] and current study showed undetectable immunoreactivity against anti-CXCL13 antibody in the epithelial cells even in the vicinity of colonizing bacteria.…”
Section: Discussioncontrasting
confidence: 43%